E-Commerce Marketplace Petshop Menggunakan Integrasi Rajaongkir API dan iPaymu Payment Gateway API - Putra, Dony Aditya; Arya Sasmita, Gusti Made; Cahyawan Wiranatha, AA.Kt.Agung (JITTER : Jurnal Ilmiah Teknologi dan Komputer; Vol 1 No 1 (2020): JITTER, Vol.1, No.1, August 2020, 2020)
Petshop is a business that engaged in providing products and services for pet needs. Petshop E-Commerce information system helps one to find various Pet Shop products and services that are in the vicinity of a particular area along with available information and with the implementation of E-Commerce Marketplaces. This system was developed with a web-based framework that implements CodeIgniter, Google Maps API, RajaOngkir API and iPaymu payment gateway API as a basis and website creation features. 30 respondents tests gave a very good and good rating of 75,75% from the interface aspect, while from the suitability features aspect of the respondents gave a very good and good rating of 82,14%.